The study of laparoscopic mini gastric bypass in patients of morbid obesity - Bansod, Atish N.; Awachar, Neha S.; Umalkar, Rohan K.; Tayade, Priyanka C.; Mirajkar, Girish N.; Patil, Ishwar (International Surgery Journal, 2022)
Background: Laparoscopic mini gastric bypass (MGB) is considered superior in terms of weight loss, co-morbidity resolution and less complications, thus improve quality of life. Methods: A prospective interventional study using laparoscopic MGB in 52 morbidly obese patient over a period of 2 years. Results: Weight loss with average percentage excess weight loss (%EWL) at the end 6 months is 72.62%, at the end of 1st year 80.55% and at the end of 2nd year it is 85.83%. Out of 15 diabetic patients, 66.66% had complete remission of Diabetes mellitus resulting in discontinuation of medications and 20% of them had partial remission. Out of the 18 hypertensive patients, 88.88% had complete remission and 5.55% of them had partial remission and other 5.55% had decrease in dosage medications. Out of 20 patients of obstructive sleep apnoea syndrome (OSAS), 75% patients had complete remission and 25% of them had partial remission. Conclusions: Laparoscopic MGB is an effective procedure with >50% EWL as early as 3 months. Laparoscopic MGB causes complete or partial remission of the comorbidities like diabetes mellitus, Hypertension and OSAS.